THE CONCEPT OF MEDIADISKURS AND THE RESULTS OF PRACTICE IN ENGLISH AND UZBEK (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article will consider specific issues of adequacy when translating artistic means from Uzbek to English and vice versa. He also studies the potential patterns of these problems with an emphasis on improving the accuracy and efficiency of translations of artistic media. Difficulties in translating artistic instruments from Uzbek to English. The translation of the means of art from Uzbek into English presents several difficulties that arise due to linguistic, technical and cultural differences between the two languages.